2014
DOI: 10.1093/neuonc/nou229
|View full text |Cite
|
Sign up to set email alerts
|

Wnt pathway in atypical teratoid rhabdoid tumors

Abstract: These promising therapeutic options will be studied further before starting a translational clinical trial. The success of these options will improve care for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…SMARCB1, which has decreased expression in ATRT tumors (28,29), appears in Cluster 1. PTK7 shows significant upregulation across all three ATRT samples and is found in the same cluster as both transcripts of WNT5B, which was previously found to be upregulated in ATRT tumor tissue (24). A gene set enrichment analysis of our four gene clusters into biological function using gene ontology (GO) shows 86 genes involved in the top ten biological processes of each cluster.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…SMARCB1, which has decreased expression in ATRT tumors (28,29), appears in Cluster 1. PTK7 shows significant upregulation across all three ATRT samples and is found in the same cluster as both transcripts of WNT5B, which was previously found to be upregulated in ATRT tumor tissue (24). A gene set enrichment analysis of our four gene clusters into biological function using gene ontology (GO) shows 86 genes involved in the top ten biological processes of each cluster.…”
Section: Resultssupporting
confidence: 57%
“…While the role that overexpression of PTK7 plays in malignancies such as colon, breast, gastric, and lung cancer has been studied, no studies to date have evaluated the role of PTK7 expression in ATRT (1723). Prior studies in this laboratory have demonstrated that the Wnt signaling pathway has a critical role in ATRT tumor growth (24), and this present study will further evaluate how components of the Wnt pathway, such as PTK7, are involved in ATRT growth.…”
Section: Introductionmentioning
confidence: 91%
“…Interestingly, an independent study using human NPC obtained from discordant dizygotic twins for congenital Zika syndrome found a similar involvement of the Wnt signaling pathway regarding differential sensitivity of NPC to ZIKV BR infection (29). Translating these results to the clinical setting, patients with aggressive AT/RT and medulloblastoma should be good candidates for a future oncolytic therapy with ZIKV BR , because Wnt pathway activation plays an important role in the biology of both tumor types (27,30), contributing to stemness and therapeutic resistance (31,32). Importantly, observed metastasis remission also suggests that a possible treatment exploring ZIKV BR oncolytic effects could benefit patients with advanced and disseminated disease.…”
Section: Discussionmentioning
confidence: 89%
“…Unbalanced regulation of Wnt signaling effectors, like CTNNB1, is common in AT/RT (27). The relevance of Wnt signaling pathway to normal neural development is also well established (28).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are few effectual treatments and surgery on children is not effective as the removal of the entire brain tumor is difficult. Recently, transcriptome profiling of malignancies of the central nervous system (CNS) have provided important insights into potential targets for therapies [ 2 , 3 , 4 ]. Here, we examine how transcriptome profiling of pediatric medulloblastomas reveals targets for potential therapies.…”
Section: Introductionmentioning
confidence: 99%